FEATURES OF THE IMPLEMENTATION OF THE POLICY OF MULTICULTURALISM (BASED ON THE EXPERIENCE OF CANADA, AUSTRALIA AND SWEDEN) - Клименко, Д. Л. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The history of the introduction of the policy of multiculturalism in Canada, Australia and Sweden was reviewed. Key documents and acts which ensure implementation of the policy of multiculturalism in these countries were analized. Programs and policy objectives developed by governments and the departments of State were studied. Actions of the institutions involved in the implementation and execution of tasks were characterized.